Opportunities and challenges for coffee production in Papua New Guinea’s highlands - Mukerjee, Rishabh; Iha, Helmtrude Sikas; Warambukia, Damaris (Australian National University, 2024)
Coffee is one of the most important smallholder cash crops in Papua New Guinea. It accounted for US$156 million of export earnings, 13% of agricultural export revenues, and 1.4% of total export revenues in PNG in 2021. According to the PNG Rural Household Survey 2023, approximately 55% of sampled households in the highlands produce coffee.